Accountability Challenges of Industrialized Economy:Potential for Enhancing Industry-Institute-Interaction - Matani, A. G.; Ahuja, Vishwas N. (Journal of Engineering Education Transformations, 2009)
Indian industries have joined hands to fine- tune their activities covered under corporate social responsibility. For this, they have to set up a global platform to showcase all the work done by Indian firms. This paper highlights various strategies adopted by different industrial organizations towards environmental protection and sustainable development in industrialized economy.